A systematic review of the institutional success factors for blockchain-based land administration. (February 2023) - Ansah, Barikisa Owusu; Voss, Winrich; Asiama, Kwabena Obeng; Wuni, Ibrahim Yahaya
Abstract: The land administration systems have witnessed many innovative technologies in the attempt to revolutionalize the task of recording land and property rights. One such revolution is the transition toward blockchain-based land administration. Like most technologies, blockchain-based land administration projects are not immune to failures, early adopters have encountered challenges, and several pilot cases have failed. Institutional factors have proven to be issues that can hinder the successful adoption of technological innovations such as blockchain-based land administration. This study identifies and analyses institutional success factors for adopting blockchain-based land administration. A systematic literature review of 37 studies resulted in the extraction of 18 related institutional factors critical to adopting blockchain-based land administration projects. Using Scott's three-pillar framework, the factors were divided into three dimensions: regulatory, organisational and cultural environment. Despite the popular opinion that the regulatory environment is integral to adopting blockchain-based land administration, our review suggests that a mutual co-existence and interplay between all the factors is key to the success of blockchain-based land projects. This study concludes that the adoption of blockchain-based land projects can be enhanced by understanding the institutional factors necessary to adopt blockchain-based land administration. Highlights: The institutional dimension for blockchain-based land administration is crucial. There are at least 18 institutional success factors for adopting blockchain-based land administration. The study derived a 3-pillar institutional framework for blockchain-based land administration. Regulative, normative and cognitive institutional support systems are required for blockchain adoption. The confluence of the systems is key to the success of blockchain-based land administration.